Crystal Structure and Density Functional Calculation of (E)-4-Hydroxy-3-methyl-N'- (thiophen-2-ylmethylene)-1,4-dihydroquinoxaline-2-carbohydrazide Radical - M. Ibrahim, Mohammad; Al-Refai, Mahmoud; N. Dawoud, Jamal; Abu-El-Halawa, Rajab; H. Massad, Mohannad; Judeh, Zaher; F. Ali, Basem (Asian Journal of Chemistry, 2012)
The compound (E)-4-Hydroxy-3-methyl-N'-(thiophen-2-ylmethylene)-1,4-dihydroquinoxaline- 2-carbohydrazide (C15H13N4O2S) is a stable free radical quinoxaline derivative. It was prepared by treatment of an acidified ethanolic solution of 3-methyl-2-(thiophen-2- ylmethylenehydrazinocarbonyl)quinoxaline-4-oxide with a solution of CuSO4.5H2O. The crystal structure shows that the molecule contains non-planar linking unit between quinoxaline and thiophene rings. Hydrogen bonding (N-H…O), p…p stacking and S…S intermolecular interactions may be effective in the stabilization of the crystal lattice. Density functional theory results agree well with X-ray experimental findings indicating that the free radical is indeed possible and that the stability of this compound might be attributed to the highly electron delocalization of the conjugation system over the whole compound along with the extra stabilization from the intramolecular interactions.